The Influence of Environmental Factors on the Development of Dengue Fever - Asnita Yani (The International Science of Health Journal, 2024)
Dengue fever (DF) remains a significant public health concern, particularly in tropical regions such as Indonesia. This narrative review explores the influence of environmental factors on the development and transmission of DF. Key environmental determinants, including standing water, temperature, humidity, urbanization, and climate change, play pivotal roles in shaping the epidemiology of DF. Poor sanitation and inadequate waste management provide breeding grounds for Aedes aegypti mosquitoes, while rising temperatures and fluctuating rainfall patterns accelerate mosquito reproduction and virus transmission. Urbanization exacerbates DF risks by fostering unplanned infrastructure development and population density, limiting green spaces essential for mosquito predator habitats. Additionally, the review highlights the critical role of family behavior and community participation in dengue prevention, particularly through education on healthy and clean living practices. Addressing these factors requires collaborative strategies, integrating public education, urban planning, and climate adaptation to mitigate DF risks effectively. This study underscores the need for sustainable, multi-sectoral approaches to manage DF, reduce its incidence, and protect public health.